2023
DOI: 10.1111/geb.13647
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiod drives cessation of wood formation in northern conifers

Abstract: Aims Shifts in xylem phenology directly determine the forest capacity for carbon sequestration. However, a systematic understanding of the spatial patterns and the underpinning drivers in determining the cessation of wood formation (Ccw) is lacking at a pan‐continental scale. Here, we addressed this knowledge gap by compiling a new dataset of multiple xylem phenology timings for northern conifers. Locations Sixty‐two study sites, Northern Hemisphere (25–55° N). Time period 2003–2018 (16 years). Taxa Thirty‐thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 174 publications
0
0
0
Order By: Relevance
“…Previous studies have reported that temperature and photoperiod were the most important determinants in regulating autumn phenology in the northern middle to high latitudes (Garner and Allard 1922, Heide 2008, Fu et al 2020, Mu et al 2023. Increasing air temperature generally has positive effects on autumn phenology in temperate and cold regions (Jeong et al 2011, Wang et al 2016, Vitasse et al 2021, Geng et al 2022.…”
Section: Introductionmentioning
confidence: 97%
“…Previous studies have reported that temperature and photoperiod were the most important determinants in regulating autumn phenology in the northern middle to high latitudes (Garner and Allard 1922, Heide 2008, Fu et al 2020, Mu et al 2023. Increasing air temperature generally has positive effects on autumn phenology in temperate and cold regions (Jeong et al 2011, Wang et al 2016, Vitasse et al 2021, Geng et al 2022.…”
Section: Introductionmentioning
confidence: 97%